The danger of interventionism: how to save brazilian liberalism in the Thatcher style - Mendes Flores, Lorena; Alves de Araújo Filho, Paulo Sérgio (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The article analyzes interventionism in Brazil after the 1988 Constitution in comparison to the post-World War II government intervention in Britain. in comparison to the post-World War II government intervention in Britain. Through this comparison, including a brief definition of interventionism and the complexity of the free market, the aim is to determine how the governmental and economic model applied in England can be adapted to the current Brazilian context. The application of Thatcherism in Brazil would imply a reduction in government functions, leading to greater efficiency by focusing on fewer concerns, as well as increasing the free market and, consequently, individual freedom to undertake and manage their finances with a significant reduction in taxes. A strong state is not one with numerous obligations but rather one that fulfills its assigned duties well, enabling individuals to make most decisions in their lives and homes without state intervention.